The Stress-Active Cell Division Protein ZapE Alters FtsZ Filament Architecture to Facilitate Division in Escherichia coli - DiBiasio, Eric C.; Dickinson, Rebecca A.; Trebino, Catherine E.; Ferreira, Colby N.; Morrison, Josiah J.; Camberg, Jodi L. (Frontiers in Microbiology, 2021)
During pathogenic infections, bacterial cells experience environmental stress conditions, including low oxygen and thermal stress. Bacterial cells proliferate during infection and divide by a mechanism characterized by the assembly of a large cytoskeletal structure at the division site called the Z-ring. The major protein constituting the Z-ring is FtsZ, a tubulin homolog and GTPase that utilizes the nucleotide to assemble into dynamic polymers. In Escherichia coli, many cell division proteins interact with FtsZ and modulate Z-ring assembly, while others direct cell wall insertion and peptidoglycan remodeling. Here, we show that ZapE, an ATPase that accumulates during late constriction, directly interacts with FtsZ and phospholipids in vitro. In the presence of ATP, ZapE induces bundling of GTP-induced FtsZ polymers; however, ZapE also binds FtsZ in the absence of GTP. The ZapE mutant protein ZapE(K84A), which is defective for ATP hydrolysis, also interacts with FtsZ and induces FtsZ filament bundling. In vivo, cultures of zapE deletion cells contain a low percentage of filamentous cells, suggesting that they have a modest division defect; however, they are able to grow when exposed to stress, such as high temperature and limited oxygen. When combined with the chromosomal deletion of minC, which encodes an FtsZ disassembly factor, zapE minC cells experience growth delays that slow proliferation at high temperature and prevent recovery. This synthetic slow growth phenotype after exposure to stress suggests that ZapE may function to ensure proliferation during and after stress, and this is exacerbated when cells are also deleted for minC. Expression of either ZapE or ZapE(K84A) complements the aberrant growth phenotypes in vivo suggesting that the division-associated role of ZapE does not require ZapE ATP hydrolysis. These results support that ZapE is a stress-regulated cell division protein that interacts directly with FtsZ and phospholipids, promoting growth and division after exposure to environmental stress.